Efektivitas Latihan Senam Jantung Sehat untuk Menurunkan Kadar Lemak pada Ibu-Ibu PKK Desa Sukowarno Kabupaten Musi Rawas - Pujiati Pujiati; Muhammad Suhdy; Hengky Remora. (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the decrease in fat levels in PKK women in Sukowarno Village after being given a Healthy Heart Gymnastics exercise. The research method used was quasi-experimental. The data collection technique in this study used a skinfold calipers body fat percentage test. Data analysis technique with normality test. Based on the survey results, the magnitude of t count is 12.63 and t table 2.056 with a significant 5% (α = 0.05) with degrees of freedom dk = n-1 where n is the number of student data as many as 27 mothers. Suppose the value of t count > t table. Then the hypothesis is accepted so that the average results of fat levels in PKK women in Sukowarno village after being given healthy heart exercise are less than the post-test average value. In conclusion, healthy heart exercise effectively reduces fat levels in PKK women in Sukowarno village, Musi Rawas district. Keywords: Decrease, fat content, healthy heart exercise,